Novel colored biomass-waste from food industry sector derived hierarchical porous carbon nanofiber for robust symmetric supercapacitor - Nursyaputri, Wan Mery; Fairuzy, Zeeva Khalilah; Khumairah, Zahra; Yanti, Novi; Nursyafni, Nursyafni; Apriwandi, Apriwandi; Taslim, Rika; Taer, Erman (Communications in Science and Technology, 2024)
A major challenge in the use of supercapacitor energy storage applications is optimizing 3D-hierarchical porous and 2D nanofiber structures to improve the electrochemical performance of colored biomass-derived activated carbon (AC). Therefore, this study aims to synthesize AC from Dracaena Angustifolia (DA) leaves and dregs using a sustainable method through chemical activation and high-temperature pyrolysis. AC was designed to be adhesive-free to maintain the true mechanical properties of the precursor. Research results showed that the sample of DA-dregs-KOH shows optimal results with a specific surface area (317.66 m2 g-1). The electrochemical performance of hierarchical porous carbon treated with 1 M H2SO4 electrolyte in a 2-electrode system had a nanofiber structure with the highest specific capacitance (248 F g-1) at 1 A g-1 and energy density (12.96 Wh kg-1) with a coulomb efficiency 84.1%. Based on these results, DA dreg-KOH based porous AC with hierarchical porous morphology shows significant potential to be used as binder-free electrode materials that can produce high-performance supercapacitors as a new renewable and sustainable energy storage solution.